Acclimation of bloom‐forming and perennial seaweeds to elevated pCO2 conserved across levels of environmental complexity. (25th April 2017) - Xu, Dong; Schaum, Charlotte‐Elisa; Lin, Fan; Sun, Ke; Munroe, James R.; Zhang, Xiao W.; Fan, Xiao; Teng, Lin H.; Wang, Yi T.; Zhuang, Zhi M.; Ye, Naihao
Abstract: Macroalgae contribute approximately 15% of the primary productivity in coastal marine ecosystems, fix up to 27.4 Tg of carbon per year, and provide important structural components for life in coastal waters. Despite this ecological and commercial importance, direct measurements and comparisons of the short‐term responses to elevated p CO2 in seaweeds with different life‐history strategies are scarce. Here, we cultured several seaweed species (bloom forming/nonbloom forming/perennial/annual) in the laboratory, in tanks in an indoor mesocosm facility, and in coastal mesocosms under p CO2 levels ranging from 400 to 2, 000 μatm. We find that, across all scales of the experimental setup, ephemeral species of the genus Ulva increase their photosynthesis and growth rates in response to elevated p CO2 the most, whereas longer‐lived perennial species show a smaller increase or a decrease. These differences in short‐term growth and photosynthesis rates are likely to give bloom‐forming green seaweeds a competitive advantage in mixed communities, and our results thus suggest that coastal seaweed assemblages in eutrophic waters may undergo an initial shift toward communities dominated by bloom‐forming, short‐lived seaweeds. Abstract : Macroalgae are primary productivity in coastal marine ecosystems and provide important structural components for life in coastal waters. Despite their ecological and commercial importance, direct measurements and comparisons of variability in the short‐term responses of different macroalgal species to elevated p CO2 are scarce and often carried out in the laboratory, where it is unclear how the results translate into more natural settings. We found that ephemeral species of the genus Ulva increased their photosynthesis and growth rates the most, whereas longer‐lived perennial species showed a smaller increase or a decrease in photosynthesis and growth rates. Our results suggest that coastal seaweed assemblages in eutrophic waters may undergo an initial shift toward bloom‐forming seaweed‐dominated communities and that short‐term laboratory measurements can predict the direction and shape of the response in more complex settings well, but the magnitude is modulated by temperature fluctuations in the outdoor and indoor mesocosm facilities.